Exacerbations and Pseudomonas aeruginosa colonization are associated with altered lung structure and function in primary ciliary dyskinesia - G. Piatti; M. M. De Santi; A. Farolfi; G. V. Zuccotti; E. D'Auria; M. F. Patria; S. Torretta; D. Consonni; U. Ambrosetti (BMC, 2020)
Abstract Background Recurrent bacterial infections of the respiratory tract are one of the major clinical features of the primary ciliary dyskinesia (PCD), a rare genetic disease due to malfunctioning of motile cilia. Chronic infections and persistent inflammation of the respiratory system result in progressive lung disease. Aim of the study was to highlight the main factors associated with clinical, functional and anatomical deterioration in PCD patients. Methods We retrospectively analyzed data from 58 patients with PCD, 37 adults and 21 children. The demographic and clinical data, forced expiratory volume at 1 s (FEV1) and forced vital capacity (FVC), sputum microbiology and imaging results (chest CT scores-modified Bhalla) were recorded. Patients were stratified according to the number of exacerbations (< 2/year vs ≥ 2/year) and chronic Pseudomonas aeruginosa (PA) colonization. The possible correlations between lung function and chest CT scores were assessed; we also evaluated the correlation between these parameters and the severity scores for bronchiectasis (BSI, FACED and e-FACED). Results Chest CT scores showed a significant correlation with FEV1 (p = 0.0002), age (p <  0.0001), BMI (p = 0.0002) and number of lung lobes involved (p <  0.0001). PA colonization had an overall prevalence of 32.6%: no significant difference in FEV1 between PA colonized and non-colonized patients was found (p = 0.70), while chest CT score was significantly worse in chronic PA colonized patients (p = 0.009). Patients with a high number of exacerbation (≥ 2/year) were older (p = 0.01), had lower FEV1 (p = 0.03), greater number of lobes involved (p < 0.001) and worse CT score than patients with low number of exacerbations (p = 0.001); they also had higher prevalence of PA chronic bronchial infection (33.3% versus 13.6%, p = 0.10). Multivariable linear regression analyses adjusted for gender, age and BMI showed positive associations between PA colonization and number of exacerbations with severity of disease (number of lobes involved, CT score, BSI, FACED, and e-FACED). Conclusions In our PCD population the number of exacerbations (≥ 2/year) and PA colonization were the two most relevant factors associated with severity of disease.